The Behavior Of Student Coffee Connoisseurs - Dwijayanti, Ratna; Fikri, Sofiul (STIE PGRI Dewantara Jombang, 2019)
This research is motivated by the phenomenon of young people with an attached coffee shop . This research is intended to find out and analyze consumer behavior factors in making purchasing decisions at Coffee Break State University of Surabaya (Unesa). This study uses qualitative research that takes the phenomenology case that occurs among young people, namely students. This study uses triangulation methods and informants from the study amounted to 5 people using purposive sampling. From the results of the study found that each informant has a different opinion and basis on each factor of the purchase decision on Coffee Break Unesa. The conclusion from this study found that the factors of consumer behavior making purchasing decisions are based on internal and external factors influencing the buying activity at Coffee Break Unesa